Assessing Online Library Guide Use and Open Educational Resource (OER) Potential: An Evidence-Based Decision-Making Approach. Issue 3 (18th August 2021) - Lauseng, Deborah L.; Howard, Carmen; Scoulas, Jung Mi; Berry, Allan
Abstract: This research aims to measure the impact of an online guide on user learning experience and to gather evidence for staffing allocations and for conversion of the guide to an open educational resource (OER). It utilizes quantitative and qualitative methods by combining usage data (Google Analytics) with a web-based user survey that incorporates the Project Outcome Model. Google Analytics data for the guide from July through December 2019 indicates 45, 324 Users for 67, 405 Pageviews. For the same timeframe, survey data (N = 119) shows that the participants were primarily students (64%) and practicing health professionals (23%). The mean scores of confidence between first-time and repeat users have a statistically significant difference on three guide pages. Combining data sources provides a more robust assessment and a clearer understanding of who users are, their behavior, and guide impact on user learning and outcomes. The high number of nonaffiliated users and the self-reported success in achieving learning outcomes reinforce the value of converting the guide to an OER. This research benefits those working in the library and educational fields by providing insights into the use of online guides as OER, the need for library-based OER, and the use of evidence to support staffing allocations.